2022
DOI: 10.15212/ijafr-2020-0153
|View full text |Cite
|
Sign up to set email alerts
|

An overview of Irish pig production, research and knowledge transfer since 1960

Abstract: Pig production in Ireland has gone through enormous changes during the past 60 yr, from pigs being primarily produced as a sideline on dairy farms, to an industry with one of the highest average herd sizes in Europe. This happened in part due to external pressure on the industry, whereby economies of scale were needed to compete with pigs produced in other countries, but largely due to the instigation of national programmes to support the pig industry through research, education and knowledge transfer. These e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…However, farrowing crates typically offer even closer confinement then gestation stalls. Boyle et al (2002b) showed that even when sows had previous experience of farrowing crates they showed lying difficulties during the first two hours on re-introduction to crates, making on average three attempts before lying down successfully. Similarly, Bonde et al (2004) found that 41% of sows in farrowing crates in 10 commercial herds showed lying difficulties.…”
Section: Resting Problems and Related Abmsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, farrowing crates typically offer even closer confinement then gestation stalls. Boyle et al (2002b) showed that even when sows had previous experience of farrowing crates they showed lying difficulties during the first two hours on re-introduction to crates, making on average three attempts before lying down successfully. Similarly, Bonde et al (2004) found that 41% of sows in farrowing crates in 10 commercial herds showed lying difficulties.…”
Section: Resting Problems and Related Abmsmentioning
confidence: 99%
“…Finally, it is worth mentioning that 5-20% of lameness is due to claw lesions (Dewey et al, 1993) Sows kept in confined conditions during lactation are often affected by injuries at weaning which occurred due to movement restrictions and bodily contact with fixtures and fittings (i.e. farrowing crates) (Boyle et al, 2002b;Bonde et al, 2004;Schmitt et al, 2019;Maschat et al, 2020). The latter authors recommend keeping the confined period around farrowing as short as possible to minimise injuries to sows (Maschat et al, 2020).…”
Section: Condition Of the Sow Post-weaningmentioning
confidence: 99%
See 1 more Smart Citation
“…In Italy, the environmental impact is related to the specialisation in production of heavy pigs, which requires a longer fattening period and restricted feeding compared to production in other European countries [34]. Over the investigated period, competitive large-scale export-orientated pig farming in Ireland benefitted from new Asian markets [35] but ASF-induced benefits have an undesired impact on the environmental dimension.…”
Section: Pig Farming Development Clusters In the Eumentioning
confidence: 99%
“…The study by [17] argues that the EU pig farming has a higher global warming potential (CO 2 e) compared to US pig farming due to dependence on imported soybeans from Brazil and Argentina, as these countries change land use and destroy forests in order to benefit from the situation. As feed represents about 70.0% of production costs [35], the development of financially attractive short feed supply chains could solve two important problems, namely reduce the reliance on imported protein and reduce GHGEs. The most recent academic studies deal with the aforementioned research niche.…”
Section: Ghge Reduction Alternativesmentioning
confidence: 99%